NANOG improves type I collagen expression in human fetal scleral fibroblasts - Li, Xuyan; Yu, Tianfei; Li, Ming; Wang, Youqi; Meng, Bo; Mu, Yanshuang (Archives of Biological Sciences, 2019)
Paper description: Human fetal scleral fibroblasts (HFSFs) are components of the sclera that are involved in eye growth regulation and myopia formation. Nanog homeobox (NANOG) is a key transcription factor essential for the pluripotent and self-renewing phenotypes of embryonic stem cells. NANOG overexpression in HFSFs improves type I collagen expression and increases proliferation rates of HFSFs. The increase in the number of HFSFs and type I collagen may delay sclera remodeling. Our findings contribute to the development of more effictive theoretical support for myopia treatment. Abstract: Human fetal scleral fibroblasts (HFSFs) are components of the sclera and play important roles in its structure and function. In myopia, scleral remodeling reduces collagen fibers and the sclera begins to thin. NANOG is a key transcription factor essential for pluripotent and self-renewing phenotypes of undifferentiated embryonic stem cells. To determine whether NANOG improves human fetal scleral fibroblast quality and the underlying mechanisms in these cells, we established stable NANOG-overexpressing HFSFs. We studied type I collagen (COL1A 1) and Rho-associated coiled-coil protein kinase 1 (ROCK1) expression in transfected cells. We also investigated POU5F1, SOX2, KLF4, MYC and SALL4 expression in NANOG stably-overexpressed fibroblasts. Our data show that NANOG expression increased proliferation rates in fibroblasts. When compared to controls, expression of COL1A 1 in transfected fibroblasts was increased and the expression of ROCK1 was decreased. Similarly, the expression of POU5F1, SOX2 and KLF4 was downregulated, the expression of MYC was upregulated and there was no significant change in the expression of SALL4 in transfected fibroblasts. Our results suggest that in fibroblasts, NANOG regulates ROCK1 expression and improves COL1A 1 expression to delay scleral remodeling. https://doi.org/10.2298/ABS180711048L Received: July 11, 2018; Revised: September 15, 2018; Accepted: October 11, 2018; Published online: October 23, 2018 How to cite this article: Li X, Yu T, Li M, Wang Y, Meng B, Mu Y. NANOG improves type I collagen expression in human fetal scleral fibroblasts. Arch Biol Sci. 2019;71(1):63-70.